Dimeric Glycoprotein VI Binds to Collagen but Not to Fibrin - Ebrahim, Mariam; Jamasbi, Janina; Adler, Kristin; Megens, Remco T. A.; M'Bengue, Yacine; Blanchet, Xavier; Uhland, Kerstin; Ungerer, Martin; Brandl, Richard; Weber, Christian; Elia, Natalie; Lorenz, Reinhard; Münch, Götz; Siess, Wolfgang (Thrombosis and Haemostasis, 2018)
Platelet glycoprotein VI (GPVI) acts as a decisive collagen receptor in atherothrombosis. Besides collagen, injured atherosclerotic plaques expose tissue factor (TF) that triggers fibrin formation. Two recent studies reported that platelet GPVI also functions as fibrin receptor, which would importantly widen the mode of action of GPVI-targeted antithrombotic drugs. We studied the binding of two GPVI fusion proteins to fibrin under static and arterial flow conditions. Fibrin was prepared from purified fibrinogen or generated more physiologically from endogenous fibrinogen by coagulating plasma with thrombin. Fibrin formation was also triggered by exposing TF-coated surfaces or human atherosclerotic plaque slices to arterially flowing blood. By binding studies and advanced optical imaging, we found that recombinant dimeric GPVI-Fc fusion proteins with Fc from either IgG1 (GPVI-Fc1) or IgG2 (GPVI-Fc2) bound to collagen fibres, but neither to fibrin prepared from purified fibrinogen obtained from three suppliers, nor to physiological fibrin formed by thrombin in plasma or triggered by exposing TF or atherosclerotic plaque slices to arterially flowing blood. Our findings do not support a role of dimeric platelet GPVI as receptor for fibrin. This is important for the understanding of plaque-triggered platelet thrombus formation and is clinically relevant for future GPVI-targeting therapies with recombinant GPVI-Fc and anti-GPVI antibodies.
Keywords: GPVI; collagen receptor; targeting drugs; GPVI-Fc; fibrin; atherothrombosis